The molecular-kinetic approach to wetting dynamics: Achievements and limitations - Sedev, Rossen (Elsevier BV, 2015)
The molecular-kinetic theory (MKT) of dynamic wetting was formulated almost 50 years ago. It explains the dependence of the dynamic contact angle on the speed of a moving meniscus by estimating the non-hydrodynamic dissipation in the contact line. Over the years it has been refined to account explicitly for the influence of (bulk) fluid viscosity and it has been applied successfully to both solid-liquid-vapour and solid-liquid-liquid systems. The free energy barrier for surface diffusion has been related to the energy of adhesion. The MKT provides a qualitative explanation for most effects in dynamic wetting. The theory is simple, flexible, and it is widely used to rationalize the physics of wetting dynamics and fit experimental data (dynamic contact angle versus contact line speed). The MKT predicts an intermediate wettability as optimal for high-speed coating as well as the maximum speeds of wetting and dewetting. Nevertheless, the values of the molecular parameters derived from experimental data tend to be scattered and not particularly reliable. This review outlines the main achievements and limitations of the MKT and highlights some common cases of misinterpretation.